Losses in soil organic carbon stocks and soil fertility due to deforestation for low-input agriculture in semi-arid southern Africa. (June 2019) - de Blécourt, Marleen; Gröngröft, Alexander; Baumann, Stephan; Eschenbach, Annette
Abstract: Woodland clearing for the expansion of low-input agriculture is an important recent land-use change in semi-arid southern Africa. We quantified the impacts of this land-use change on the concentrations and stocks of soil organic carbon (SOC), soil nutrients and soil fertility in NE Namibia and SW Zambia. In total, we selected 11 sampling clusters, each cluster containing up to three sampling plots in agricultural fields (field age ranged from 2 to 26 years) and one reference plot in woodland. The conversion from woodland to low-input agriculture affected the concentrations of SOC, total N and exchangeable Mg in the soil. These changes were also apparent in the cumulative losses of stocks of exchangeable Mg to 40 cm and of SOC and N to 100 cm depth. Likewise maize yields predicted by the QUEFTS model declined by ∼15% in old agricultural fields, indicating a decrease in soil fertility. The impacts of land-use change were most evident in the Namibian area, where the mean SOC losses up to 100 cm depth in old agricultural fields were 9.6 Mg C ha −1, which corresponds to 20% of the original stocks in woodland. The losses of soil fertility indicate that current agricultural management is not sustainable. Highlights: Replacing woodland by low-input agriculture alters topsoil SOC and nutrient levels. Loss in stocks of exchangeable Mg to 40 cm, and of SOC and N to 100 cm depth. The loss in SOC and soil nutrients increases with field age. Loss in soil fertility illustrated by a decline in predicted maize yields.